Direct costs of a home parenteral nutrition programme. Issue 4 (August 2019) - Arhip, L.; García-Peris, P.; Romero, R.M.; Frías, L.; Bretón, I.; Camblor, M.; Motilla, M.; Velasco, C.; Morales, A.; Carrascal, M.L.; Herranz, A.; Sanjurjo, M.; et al.
Summary: Background & aims: Home parenteral nutrition (HPN) is a lifesaving treatment for people with chronic intestinal failure and its cost has been reported to be very high. The purpose of the present paper was to study the direct healthcare and non-healthcare costs associated with the HPN programme managed by a tertiary hospital. Methods: Observational, retrospective study of all adult patients on HPN from 11.1.2014 to 10.31.2015 treated at Gregorio Marañón University Hospital (Madrid, Spain). An economic evaluation was undertaken to calculate the direct healthcare (HPN provision, outpatient monitoring and management of complications) and non-healthcare costs (transportation process) of the HPN programme. The variables were collected from medical records, the dispensary and the hospital's financial services. The unit costs were taken from official price lists. Results: Thirty-two patients met the inclusion criteria. Total direct healthcare and non-healthcare costs amounted to €13, 363.53 per patient (€124.02 per patient per day). The direct healthcare costs accounted for 98.32% of overall costs, while the non-healthcare costs accounted for the remaining 1.68%. HPN provision accounted for the majority of the costs (74.25%), followed by management of complications (21.85%) and outpatient monitoring (2.23%). Conclusions: The direct healthcare costs accounted for the majority of HPN expenditure, specifically HPN provision was the category with the highest percentage.